Leucinostatins target Plasmodium mitochondria to block malaria transmission - Guodong Niu; Xiaohong Wang; Jun Li (Parasites & Vectors, 2024)
Abstract Background Malaria remains a critical disease. Leucinostatins from the fungus Purpureocillium lilacinum inhibited the transmission of Plasmodium falciparum to mosquitoes via contact. Methods Here, we modified the leucinostatin B (LB) C-terminus to make derivatives and examined their inhibition against malaria transmission to mosquitoes. Fluorescence-labeled leucinostatins were incubated with intact gametocytes and were examined under microscopy to detect the targets of leucinostatins. We also analyzed leucinostatins’ general cytotoxicity and hemolysis. Results The results showed that the derivatives with –H, –CH3, –Atto495, and –Biotin at C-terminus had EC50 of 1.5 nM, 0.2 nM, 4.2 nM, and 42 nM, respectively. Atto495 and biotin are similar in size and much bigger than -CH3 and -H. Based on reverse-phase HPLC elution time, we found that LB-Biotin had much higher hydrophobicity than the others, consistent with its lowest malaria transmission-blocking activity. Fluorescence microscopy showed that LB-Atto495 colocalized with mitochondria inside intact P. falciparum gametocytes. We found that leucinostatin A significantly inhibited the proliferation of human nucleated cells with IC50 around 47 nM and it did not lyse erythrocytes at 100 μM. Conclusions We conclude that the leucinostatins pass through the cytoplasmic membrane without lysing cells and interact with molecules specifically in mitochondria. Therefore, leucinostatins should be ideal inhibitors against mobile parasites, such as ookinetes and sporozoites, during malaria transmission. Graphical Abstract